2021
DOI: 10.15835/nbha49312393
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in two Aronia melanocarpa cultivars’ berries during the harvest season

Abstract: Biochemical changes that undergo during the harvest season in 2020 (between 28 July and 11 September) were evaluated by a comparative study of two Aronia cultivars. The experiment was conducted at the Research Institute for Fruit Growing Pitesti, Arges County, Romania, on ‘Melrom’ and ‘Nero’ cultivars. Dry matter, total soluble content, pH, vitamin C, and biologically active components such as anthocyanins and phenolics variations were assessed from 28 July to 11 September 2020, for berries harvested every fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…During ripening, the dry matter increased considerably (by 38.6%) in the initial stages of development (from May to June), then decreased by 32.5% in July, and remained fairly constant in August (Table S1). Mazilu et al [26] observed an increase by about 33% in the dry matter content of chokeberry fruits from 27 July to 22 August in Romania. On the other hand, the changes in the dry matter content of fruits from South Korea harvested in June and August varied, depending on the variety, and ranged from 14.60% to 48.60% [20].…”
Section: Macronutrients Of Chokeberry Fruits At Different Stages Of D...mentioning
confidence: 98%
See 1 more Smart Citation
“…During ripening, the dry matter increased considerably (by 38.6%) in the initial stages of development (from May to June), then decreased by 32.5% in July, and remained fairly constant in August (Table S1). Mazilu et al [26] observed an increase by about 33% in the dry matter content of chokeberry fruits from 27 July to 22 August in Romania. On the other hand, the changes in the dry matter content of fruits from South Korea harvested in June and August varied, depending on the variety, and ranged from 14.60% to 48.60% [20].…”
Section: Macronutrients Of Chokeberry Fruits At Different Stages Of D...mentioning
confidence: 98%
“…The analysis of anthocyanins content confirmed that the analyzed ripe black A. melanocarpa fruit was a rich source of these pigments. Mature chokeberry fruits contained total anthocyanins in the range of 0.64-3.92 g/100 g DW [3,26,33].…”
Section: Antioxidants Of Chokeberry Fruits At Different Stages Of Dev...mentioning
confidence: 99%
“…In the present study, the authors selected chokeberry as the object of study. Chokeberry (Aronia melanocarpa) is a deciduous shrub native to eastern North America and Canada, whose cultivation spread to Europe after the 19th century [1,2], due mainly to the interest in its antioxidant compounds [3]. Chokeberry is a deciduous shrub belonging to the Rosaceae family.…”
Section: Introductionmentioning
confidence: 99%
“…After that, the fruit became visibly dehydrated, but without abscission. Thus, harvesting can be planned based on the dynamics of the level of biologically active components, and also the degree of the dehydration of chokeberry fruits [3].…”
mentioning
confidence: 99%